Evaluation of Accumulation of Lead and Cadmium in the Blood and Urine of Khat- Chewers in Some Areas of Ibb Governorate, Yemen - Alhemiary, Nabil Abdurakeb; Mohammed, Bassam Yahya Abdu; Abdallah, Salah Mohammad (Journal of medical and pharmaceutical sciences, 2019)
In this study, the accumulation of lead and cadmium in blood and urine was estimated at 160 specimens aged 15- 60 years., samples were collected from different areas of Ibb governorate (Jebla, Aldehar, Almashna and Alssani), and flame atomic absorption spectroscopy was used to estimate these elements. The study effects of factors associated with the chewing khat and its impact on increase in accumulation of lead and cadmium (sex, age, daily time for chewing khat period, number of chewing years, amount of khat chewing a day, residential area, smoking and types). The highest concentration of lead in blood and urine in khat chewers was 97.297, 48.772 µg/L, cadmium 12.791, 17.577 µg/L. The accumulation rate of those who chew khat is higher than those who don't chew khat 267.50%, 245.71% for lead and 412.9%, 273.3% for cadmium. The accumulation of lead and cadmium increases in males more than females 23.78%, 33.63 in blood, 27.73%, and 17.73% in urine. Increasing age and the amount of khat chewing a day, and the time of chewing khat daily hours and the number of years increases accumulation of lead and cadmium in blood and urine from chewing of khat (P 0.05). The effect of smoking factor associated with process of chewing khat leads to increased accumulation of elements in blood and urine smokers than other factors. The highest concentration of lead in the blood and urine samples in the group of people who chew khat and smoke cigarette and madaah 114.925, 146.237, 59.087, 83.623 µg/L respectively, and increase rate of accumulation of when chewing khat and smoking. Cadmium higher concentration in blood and urine samples who chew khat and cigarette smokers 21.025, 27.136 µg/L, and it's accumulation in who chew khat and smokers than who chew khat and non- smokers increased by 157.28%, 199.54%.
Keywords: khat chewing; Accumulation of Lead and Cadmium; blood; urine; Yemen